2021
DOI: 10.1128/aac.01146-20
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Arenaviruses by Combinations of Orally Available Approved Drugs

Abstract: Neglected diseases caused by arenaviruses such as Lassa (LASV) and filoviruses like Ebola (EBOV) primarily afflict resource-limited countries, where antiviral drug development is often minimal. Previous studies have shown that many approved drugs developed for other clinical indications inhibit EBOV and LASV and that combinations of these drugs provide synergistic suppression of EBOV, often by blocking discrete steps in virus entry. We hypothesize that repurposing combinations of orally administered approved d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 77 publications
0
42
0
Order By: Relevance
“…Furthermore, given our knowledge of ribavirin treatment in other arenavirus infections, in which it is only partially effective and associated with significant side effects, investigations into uncovering effective and safe arenavirus therapeutic options are badly needed [ 7 ]. High-throughput screening assays utilizing recombinant reporter viruses as surrogates for the wild-type parental virus have previously been successful in identifying several anti-mammarenavirus compounds [ 15 , 16 , 46 , 47 ]. Here, using a novel recombinant reporter LUJV, we were able to identify six compounds with high efficacy against LUJV that warrant further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given our knowledge of ribavirin treatment in other arenavirus infections, in which it is only partially effective and associated with significant side effects, investigations into uncovering effective and safe arenavirus therapeutic options are badly needed [ 7 ]. High-throughput screening assays utilizing recombinant reporter viruses as surrogates for the wild-type parental virus have previously been successful in identifying several anti-mammarenavirus compounds [ 15 , 16 , 46 , 47 ]. Here, using a novel recombinant reporter LUJV, we were able to identify six compounds with high efficacy against LUJV that warrant further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…While emergence of drug resistance is less certain for acute viral infections, which are usually eliminated by the acquired immune response ( 16 ), SARS-CoV-2 and influenza infections in immunocompromised hosts are notable for prolonged viral persistence at high viral loads with considerable ongoing viral mutagenesis ( 60 65 ). Thus, developing combination therapies for acute viral infections is justified, and efforts are under way for influenza virus ( 66 ), Ebola virus ( 47 , 48 , 67 , 68 ), arenaviruses ( 69 ), and SARS-CoV-2. For Ebola virus, computational modeling ( 48 ) has suggested that combinations would provide superior in vivo activity to their single agent components.…”
Section: Highly Effective Drug Combinations Against Other Virusesmentioning
confidence: 99%
“…5 days post-treatment, cells were lysed with 1% Triton-100 to obtain the background values. Ribavirin is the compound demonstrating the highest relative safety with a therapeutic index of 4.9 × 10 5 :1, while favipiravir has a lower therapeutic index of To evaluate antagonistic or synergistic effects, we used the Bliss independence model, which states that two drugs have an independent effect, and their combination is calculated based on the probability of independent events [26][27][28]. As ribavirin and favipiravir have been demonstrated to block infection via distinct modes of action, they are considered to act independently [23].…”
Section: Additive Effect Between Ribavirin and T-705 In Inhibiting Hantavirus Replicationmentioning
confidence: 99%